THE VISIBILITY OF THE ENFORCEMENT AGENCY INTEGRITY COMMISSION (EAIC) IN STRENGTHENING THE PUBLIC SECTOR’S CULTURE - Irma Wani Othman; Saifulazry Mokhtar; Mohd Sohaimi Esa (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
As a Federal Statutory Body established by an Act of Parliament and gazetted on 3 September 2009 under Section 3 of the Enforcement Agency Integrity Commission Act 2009 [Act 700], the Enforcement Agency Integrity Commission (EAIC) is viewed as having a prominent role in enhancing the culture of integrity. The main purpose of this paper is to discuss the issues of integrity leakage currently facing by the EAIC including (i) Issues Concerning the Cultivation of Bribery Rewards and Corrupt Practices Among Civil Servants, (ii) Issues of Empowering Integrity Education in Sustainable Public Sector Governance, (iii) The Issue of Bureaucracy in Impairing the Efficiency of Human Resources and weakening the Organisational Administrative System, and (iv) The Issue of Exploitation by the Department’s Top Management for Personal Gain, and (v) The Issue of Cartels in Preventing the Loss of National Treasures. This paper applies secondary sources, such as research results published in journals, scholarly writing, online news sources, and public forums, to employ a qualitative methodology. According to the findings of the study found that civil servant’s breach of integrity is a serious concern if corruption and malpractice continue to occur. The study suggests that if the present system in the organisation is plagued by bureaucracy-related issues, it will worsen the situation of integrity in the government, resulting in the paralysis of the country’s governance delivery system. Hence, the crisis of integrity resulting from abuse of power, corruption, and breach of trust which can be interpreted as a frequent betrayal of trust among governments, civil servants, the private sector, and the general public places the nation at risk of having governance systems that are unreliable.